KIE Probiotik Pangan Lokal serta Manfaatnya di PMB Muzilatul Nisma Kota Jambi - Suci Rahmani Nurita; Tuhu Perwitasari; Sirly Patriani; Ova Jayanti (Jurnal Abdimas Kesehatan (JAK), 2023)
According to the 2018 National Riskesdas Report, the incidence of infectious diseases in infants aged less than 1 year consists of 10.6% diarrhea, 9.4% ISPA, and 3.8% pneumonia. As much as 70% of the body's immune system is affected by the health of the digestive system. One effort to maintain digestive health is to consume food or drinks that contain probiotics. Probiotics can be obtained from local food, namely fermented foods such as tempeh, pickles, tempoyak, tauco and tape. The purpose of implementing this educational activity is to change knowledge about local food probiotics. Community Service Activities will be held on January 13, 2023 beginning with an opening (introduction, time contract, explanation of objectives and materials to be provided and distribution of pre-test questionnaires), followed by educating participants about local food sources of probiotics and their benefits and ending with closing (distribution leaflets, distribution of post-test questionnaires, and distribution of gifts). This activity was attended by approximately 15 participants at PMB Muzilatulnisma. The results of the analysis of the pre and post test questionnaires on 9 participants, there was an increase in the participants' knowledge from before the educational activity and after the educational activity. The results of the evaluation during the educational process were that the participants seemed enthusiastic about the counseling material, the participants listened to the counseling carefully and the participants asked questions related to the material that was not clear. It is hoped that mothers can implement the knowledge gained in order to be able to consume local food sources of probiotics that exist around the community.